(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Biotinidase deficiency is a rare genetic disorder brought out by BTD (Biotinidase gene) mutations. Genetic disorders are not curable but there are drugs available for suppressing Biotinidase deficiency. To overcome this problem a vaccine that is much more effective is needed. The goal of the current research is to construct an effective multitudinous epitope-based vaccine. Biotinidase protein was chosen as an objective; various epitopes like T-cells and B-cells were anticipated. Predicted epitopes were shown stability, anti-allergenic, epigenetic, and responsive. Finalist epitopes were significantly antigenic and overlapped. Using In silico Techniques, we predicted the Primary, secondary, and tertiary structures, as also consistency, ligand-receptor association, and MHC class I and II affinity qualities for vaccine designing. The designed vaccine shows high affinity with the human receptors IL-2 alpha and a beta chain. The sequence was then cloned into the plasmid pET-28a. To improve activation in a prokaryotic cell. Docking studies further demonstrated that the forecasted peptides interacted with the HLA-B7 allele. The predicted vaccine could be a promising starting point for vaccine development against genetic disorders. Furthermore, the suggested vaccine must be subjected to in vitro experiment and further confirm to verify its immunogenic and safety profile.